The other Americans - Lalami, Laila (Bloomsbury, 2019)
"From the Pulitzer Prize finalist, author of The Moor's Account--a timely and powerful new novel about the suspicious death of a Moroccan immigrant that is at once a family saga, a murder mystery, and a love story, all of it informed by the treacherous fault lines of American culture. Nora Guerraoui, a jazz composer, returns home to a small town in the Mojave after hearing that her father, owner of a popular restaurant there, has been killed in a suspicious hit-and-run car accident. Told by multiple narrators--Nora herself, Jeremy (the Iraq war veteran with whom she develops an intimacy), widow Maryam, Efrain (an immigrant witness to the accident who refuses to get involved for fear of deportation), Coleman (the police investigator), and Driss (the dead man himself), The Other Americans deftly explores one family's secrets and hypocrisies even as it offers a portrait of Americans riven by race, class, and religion, living side by side, yet ignorant of the vicissitudes that each tribe, as it were, faces" --